Pengaruh Faktor Psikologis Terhadap Keputusan Penggunaan Jasa Pada Kereta Api Argo Muria PT. Kereta Api Indonesia (Persero) Daerah Operasi IV Semarang - Shofa Nur Masruroh; Sri Suryoko; Andi Wijayanto (Universitas Diponegoro, 2014)
The development of consumer necessaries cause the growth of transportation bussiness in Indonesia. PT KAI as the one of transportation service company offer Argo Muria excecutive train that serve Semarang – Jakarta route.The aim of this research is to know the effect of the psychological factors that consist of motivation, learning, and attitude to the purchasing decision of Argo Muria customers with 100 respondents as sample. Sampling was purposive sampling technique. The type of this research is explanatory research with primary data collection through questionnaires. Analysis techniques used linier regression with SPSS version 15. The research conclude that simultaneously learning and attitudes have significant effect to the purchasing decisions. Partially, the influence of motivation on purchasing decisions is 21,8%, learning to the buying decision is 31,5%, and the attitude towards purchasing decisions is 33,5%. Simultaneously the influence of motivation, learning, and attitudes towards purchasing decision is 45,3%Researchers suggest to PT. KAI especially Argo Muria train to maintain the excellent services and improve the timeliness of trains arriving at the destination and train cleanliness.